Role of long non-coding RNA in regulatory network response to Candidatus Liberibacter asiaticus in citrus - Zhuo, Xiaokang; Yu, Qibin; Russo, Riccardo; Zhang, Yi; Wei, Xu; Wang, Yuanzhi Zimmy; Holden, Paige Marie; Gmitter, Fred G. (Frontiers in Plant Science, 2023)
Long non-coding RNAs (lncRNAs) serve as crucial regulators in plant response to various diseases, and very few of them have been systemically identified and characterized in response to citrus Huanglongbing (HLB) caused by Candidatus Liberibacter asiaticus (CLas) bacteria. Here, we comprehensively investigated the transcriptional and regulatory dynamics of the lncRNAs in response to CLas. Samples were collected from leaf midribs of CLas- and mock-inoculated HLB-tolerant rough lemon and HLB-sensitive sweet orange at week 0, 7, 17, and 34 following inoculation using CLas+ budwood of three biological replicates in the greenhouse. A total of 8,742 lncRNAs, including 2,529 novel lncRNAs, were identified from RNA-seq data with rRNA-removed from strand-specific libraries. Genomic variation analyses of conserved lncRNAs from 38 citrus accessions showed that 26 single nucleotide polymorphisms (SNPs) were significantly correlated with HLB. In addition, lncRNA-mRNA weighted gene co-expression network analysis (WGCNA) showed a significant module correlated with CLas-inoculation in rough lemon. Notably, the most significant LNC_28805 and multiple co-expressed genes related to plant defense in the module were targeted by miRNA5021, suggesting that LNC28805 might compete with endogenous miR5021 to maintain the homeostasis of immune gene expression levels. Candidate WRKY33 and SYP121 genes targeted by miRNA5021 were identified as two key hub genes interacting with bacteria pathogen response genes based on the prediction of protein-protein interaction (PPI) network. These two genes were also found within HLB-associated QTL in linkage group 6. Overall, our findings provide a reference for a better understanding of the role of lncRNAs involved in citrus HLB regulation.